Development of a new 360-degree surface topography application - Michalik, Roman; Siebers, H.; Eschweiler, J.; Quack; Gatz, M.; Dirrichs, T.; Betsch, Marcel (Gait & Posture, 2019)
Background: Surface-topography has been used for almost two decades in the radiation-free clinical evaluation of spinal posture. So far, it was limited to the analysis of back surface and spine. In order to better understand, diagnose and treat complex spinal pathologies, it is important to measure the whole torso. Research question: Purpose of this study was to introduce and test an application that allows 360° reconstruction and analysis of the patient's torso. Methods: The application uses the information gathered from eight distinct scans and angles. For validation we used an Alderson phantom as an anthropomorphic body. Defined areas and volumes were measured by CT and surface-topography. Inter- and intra-rater reliability was tested in 35 healthy subjects by two observers. Results: The results revealed good correspondence between systems in the imaging and evaluation of the Alderson model (5.3–0.5%). Inter- (0.9–0.98) and intra-rater reliability (0.8–0.95) testing revealed good and excellent results in the detection of almost all body surface structures and measurement of areas and volumes. Only area and volume measurements using jugular notch as a reference showed partly moderate results in reliability (0.62–0.93) testing. Significance: We were able to introduce a novel 360° torso scan application using surface topography to reconstruct torso measurements. The results of our study showed its high validity and reliability. In the future, this application needs to be tested in patients with spinal pathologies. In summary, this new application may help to better understand, diagnose and treat patients with pathologies of torso and spine.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Posture; Rasterstereography; Scoliosis; Spine; Surface topography; Whole-body scanner